Perencanaan Peningkatan Produktivitas Dengan Menggunakan Metode American Productivity Center (APC) - Chandrahadinata, Dody; Jainul Hayat, Encep; Zulvia Risti, Lutfi (Jurnal Kalibrasi, 2025)
This study aims to measure and plan productivity improvements at PD Dodol Gisan using the American Productivity Center (APC) method. The main problem is the lack of a data-based productivity measurement and evaluation system. The American Productivity Center (APC) is used to calculate the productivity index (IP), profitability (IPF), and price improvement (IPH). The results show that labor IP decreased by an average of 4%, materials fluctuated (96.02 - 105.21), while energy and capital increased by 13.56% and 9.45% respectively from the baseline. The IPF showed a similar pattern, with a decline in materials of up to 11.6% and a consistent increase in energy and capital. The average IPH was 1.0, indicating that profitability was not affected by selling prices but rather by operational efficiency. Fault Tree Analysis (FTA) revealed the main factors behind the decline, namely raw material waste, high absenteeism, energy waste, and lack of equipment maintenance. Improvement planning using the 5W1H method resulted in recommendations for simple SOPs related to raw materials, workforce attendance, energy, and machine maintenance. This study provides a quantitative and practical basis for small industries to improve efficiency and profitability in a sustainable manner.